Soliton microcomb based spectral domain optical coherence tomography - Paul J. Marchand (Nature Portfolio, 2021)
Superluminescent diodes, that provide a broadband spectrum are typically used in spectral domain coherence tomography. Here, the authors use chipscale silicon nitride resonators to generate soliton microcombs with a lower noise flor that could substitute the diode sources.